Personal experience with abortion: a determining factor in Physician's attitudes towards abortionAJOG Global Reports at a Glance - Reagan M. Ingoma, MD, MPH; So Yoon Kim, PhD; Erick N. Kamangu, PhD (AJOG Global Reports, 2025)
Background: The increase in illegal abortions raises concerns about the role of physicians in providing safe abortion care. Understanding physicians' views in multicultural countries like the DRC is essential, even though the Maputo Protocol permits safe abortion care. The research aims to determine the impact of their experience with abortion on their attitudes towards abortion. Method: This is cross-sectional study involving 265 physicians from The Democratic Republic of Congo, conducted between April 1st and June 30th, 2024, using a convenience sampling technique that determines doctors' attitudes toward abortion to lay the groundwork and pave the way for future research on this issue. The study used a chi-square test to analyze categorical variables, Spearman correlation with 2 hypotheses, and multinomial logistic regression to predict the connection between the explanatory, the confounding variables, and the physician attitudes towards abortion. Results: On a scale of 1−5, the median score was 3, the mean was 2.95, and the standard deviation was 0.661. We found a significant correlation between physicians' personal experiences with abortion and their attitudes toward the practice (rs 0.211, P.001). Doctors who have personally experienced abortion are more likely to support abortion rights than pro-life doctors (OR: 6.52, P.005). Conclusion: Targeted training programs for healthcare providers on the medical, legal, and ethical aspects of abortion care are crucial for equipping them with essential knowledge and skills. Public health initiatives should create and share standardized protocols for abortion care to ensure consistent quality across all healthcare facilities, especially in rural and underserved areas, promoting equitable access to such services.